Cross sectional TEM analysis of duplex HIPIMS and DC magnetron sputtered Mo and W doped carbon coatings. (September 2015) - Sharp, J; Muller, I Castillo; Mandal, P; Abbas, A; West, G; Rainforth, W M; Ehiasarian, A; Hovsepian, P
Abstract: A FIB lift-out sample was made from a wear-resistant carbon coating deposited by high power impulse magnetron sputtering (HIPIMS) with Mo and W. TEM analysis found columnar grains extending the whole ∼1800 nm thick film. Within the grains, the carbon was found to be organised into clusters showing some onion-like structure, with amorphous material between them; energy dispersive X-ray spectroscopy (EDS) found these clusters to be Mo- and W-rich in a later, thinner sample of the same material. Electron energy-loss spectroscopy (EELS) showed no difference in C-K edge, implying the bonding type to be the same in cluster and matrix. These clusters were arranged into stripes parallel to the film plane, of spacing 7-8 nm; there was a modulation in spacing between clusters within these stripes that produced a second, coarser set of striations of spacing ∼37 nm.